Survey Of Coaching Program And Nutritional Status In Kancil Mas Karawang Football Players - Maulana, Ilham; Aulia, Dany; Setiawan, Muhammad Arief; Wijaya, Habibi Hadi; Dewi, R. Retna Kinanti (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study examined the quality of training programs and the nutritional status of young athletes at SSB Kancil Mas Karawang, a football school in Indonesia. The study used a quantitative descriptive method, utilizing structured surveys, tests, and field measurements to assess football skills and physical fitness. The study participants included 25 athletes, with data collected on November 13, 2024. Football skills were evaluated using dribbling, short passing, heading, and shooting tests, in addition to physical tests such as push-ups, sit-ups, and back-ups. Nutritional status was measured using Body Mass Index (BMI). The results showed that most athletes showed moderate to good physical abilities, but had significant deficits in heading skills (80% in the “poor” category) and shooting accuracy. Dribbling emerged as a strong skill, with 72% achieving “very good” results. Nutritional analysis revealed that all participants were underweight for their height, highlighting the need to improve a balanced diet. This imbalance affects endurance and increases the risk of injury, emphasizing the role of proper nutrition in athletic development. These findings highlight the importance of integrating science-based structured training and nutritional guidance into youth football programs to foster optimal physical and technical skills. The study offers actionable recommendations for improving training and nutrition, contributing to the broader development of football training in Indonesia.